Sosialisasi Pencegahan Cedera Olahraga Pada Siswa Kelas IV SDN Inpres Bertingkat Waena: Pengabdian - Siane Maria Tampi; Fazryani Mazita Torano; Dodi Fensi Patty (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The main objective of this program is to improve the knowledge, awareness, and skills of fourth-grade students at SDN Inpres Bertingkat Waena in preventing sports injuries through interactive and contextual socialization activities. This activity also aims to provide educational recommendations to teachers and schools so that injury prevention becomes part of physical education routines. The benefits of this program are not only experienced by students through enhanced sports health literacy but also by schools in fostering a safe sports culture that supports children’s holistic development. More broadly, this program represents a tangible contribution to promoting an active and healthy lifestyle among elementary school students. The evaluation results showed an increase in students’ understanding of the basic concepts of sports injury prevention. Students were able to explain simple steps that can be taken before and after exercising, as well as demonstrate positive attitudes toward incorporating these practices into their daily activities. Teachers also expressed full support and readiness to integrate the socialization materials into physical education lessons.